PWE-033 Presentation and surgical interventions for crohn's diseasewith perianal fistula in the biologics era: results from a multicentre study. (17th June 2017) - Black, C; Pugliese, D; Sahnan, K; Hart, A; Fiorino, G; Armuzzi, A; Katsanos, K; Christodoulou, D; Selinger, C; Maconi, G; Kopylov, U; Bosca-Watts, M; et al.
Abstract : Introduction: Introduction of biologics particularly anti-TNF agents are thought to have resulted in changes in natural history of Crohn's disease (CD). The impact of these in presentation of CD with perianal fistula (CD-PAF) and subsequent surgical approaches is not known. Method: 11 IBD centres across Europe and Israel were invited to collect data on CD-PAF patients diagnosed since January 2010 to Dec 2015. Data on demographics, mode and route of presentation, type of fistula, MRI, prior treatment for CD were collected. Patients who had at least one surgical therapy for CD-PAF fistula were analysed for reasons and the type of interventions. Results: 253 patients with CD-PAF (161 M, 92 F) were included. The mean age at diagnosis of CD was 28 years (SD: 13.3), and at diagnosis of CD-PAF was 32 years (SD: 13.92). 65% of the patients with CD-APF developed their fistulae in the period between 1 year before and 4 years after diagnosis of CD. 30% of patients were smokers at the onset of CD-PAF. 37.2% of the CD-PAF presented as emergency medical or surgical admission and 30% and 23.7% were identified in IBD clinics and colorectal clinics respectively. 77.1% has MRI pelvis done at diagnosis with 52.8% of patients having complex fistulae (38.7% trans-sphincteric, 10.3% extrasphincteric, 3.8% with suprasphincteric).Proctitis and anal stenosis at presentation were identified in 43.1% and 9.5% respectively. Examination under Anaesthesia (EUA) +/- abscess drainage was required in 69.6% of patients but only 53.8% had Seton inserted at first EUA (median number of Setons=1, range 1–6). 96 patients (68% of those needing Seton insertion) had them removed and only 33 of these needed Seton re-insertion. he reasons for non-removal:surgeons' preference (21);surgeon and physician preference (13) and patient preference (5).Overall repeat surgical intervention were required in 102 patients (40.3%):repeat abscess drainage (43), Reinsertion of Seton (33), Diverting stoma (20) and proctectomy (6). Conclusion: Majority of CD-PAF present within 5 years of their diagnosis of CD with a third presenting as emergency. EUA with abscess drainage and Seton insertion is the main surgical intervention needed. Radical surgery appears to be less often requiring in comparison to previous studies. Disclosure of Interest: None Declared